Post-Method Pedagogy: Do not use any Teaching Procedure - Hasanah, Uswatun; Sugirin (IQRO: Journal of Islamic Education, 2024)
The post method is an excellent educational innovation, particularly in the learning process between teachers and students. Why is it like that? Because post-method pedagogies believe they assist teachers in developing strategies appropriate for their students' learning context. This is very beneficial for ELT because, as we know, many students in Indonesia are not interested in learning English. They think English is not important and challenging to learn and understand. The role of the educator in the classroom as a mediator is to ensure that students receive the best education possible. Post-method pedagogy centres language learning and teaching on the teacher and respects his or her beliefs, experiences, and knowledge. Lecturers should be valued because people are also the ones to blame. In this paper, the researcher used a qualitative research design and the Library Research method. In the context of research, the term "library research" refers to the process of gleaning information and facts from a variety of library resources, such as reference books and periodicals, comparable findings of earlier studies, articles, notes, and countless magazines related to the problem that must be solved. The teacher's role is to be actively involved in the learning process and implement the defined learning processes in order to facilitate consistent learning outcomes. Furthermore, the instructor can reflect on their teaching effectiveness and alignment with the current curriculum. The teacher has a pivotal role in determining the success of the learning process. Keywords: post method, teaching. ELT